Improving speed to handball players - Georgescu, A.; Varzaru, C.; Rizescu, C. (Revista Romaneasca pentru Educatie Multidimensionala, 2019)
I chose this theme because the sporting value of a handball player largely resides in the qualities of training, including the speed that shapes and refines the principles and skills required by content development. Technical and tactical preparation is specific to the modern handball game practiced by the best teams in the world.